HIV incidence among men who have sex with men using geosocial networking smartphone application in Beijing, China: an open cohort study - Guo-Dong Mi; Bin-Bin Zhang; Fei Yu; Xian-Long Ren; Jason J. Ong; Ya-Qi Fan; Feng-Hua Guo; Chun-Jun Li; Mian-Zhi Zhang; Min-Ying Zhang (BMC, 2021)
Abstract Background Sexual transmission among men who have sex with men (MSM) is the dominant route of HIV transmission in China. Extensive use of geosocial networking (GSN) smartphone application (app) has dramatically changed the pattern of sexual behaviors and HIV risk among MSM, but data on HIV incidence and the changing risk behaviors of GSN app-using MSM are limited. We aims to assess the HIV incidence and its correlates among gay GSN app-using MSM in China. Methods We constructed an open cohort which was initiated and maintained using a GSN app to assess the HIV incidence among app-using MSM, recruited from June 2017 to December 2018. MSM completed an online questionnaire on their sociodemographic characteristics, sexual behaviors, recreational drug use and sexually transmitted infections status. Then each man had an HIV test, and those tested negatives were enrolled into the cohort. Participants completed follow-ups with additional HIV tests though the app during the study period, and were censored at HIV seroconversion or study end date. HIV incidence was calculated by dividing the sum of observed HIV seroconversions by the observed person-time. Univariate (Chi-square test and Fisher's exact test) and multivariate (proportional hazards regression) analyses were used to examine correlates of HIV incidence. Results A total of 6957 HIV negative MSM were enrolled in the open cohort, 37 seroconversions occurred among 1937 men contributing 1065 observed person-years: HIV incidence was 3.47 per 100 person-years [95% confidence interval (CI): 2.37-4.57]. More than five sexual partners [hazard ratio (HR) = 2.65, 95% CI: 1.04-6.67], and sex with HIV positive partners (HR = 3.82, 95% CI: 1.16-12.64) in the preceding six months were positively associated with HIV seroconversion. Consistent condom use for anal sex (HR = 0.27, 95% CI: 0.07-0.96), and reporting insertive anal sex only (HR = 0.23, 95% CI: 0.08-0.62) in the preceding six months were protective factors for HIV seroconversion. Conclusions Tailored interventions targeting app-using MSM are urgently needed given their high risk of HIV. As a new tool for accessing MSM at higher HIV risk, GSN smartphone app could play an important role in HIV research among MSM.